STRATEGI PERBANKAN SYARIAH INTERNASIONAL PADA PERKEMBANGAN EKONOMI DALAM MENGHADAPI TANTANGAN FINTECH DAN DIGITALISASI - Khaidar Rahmaini Jamila; Dian Zahra Syahfitri Lubis; Keisya Putri Balqis; Yabib Fikri Rambe (Yayasan Baitul Hikmah al-Zain, 2026)
The transformation of the global financial system has seen major changes from the increasing use of digital technology in a number of economic activities. Islamic banking at the international level is experiencing a new situation marked by cross-border competition, shifting customer behavior patterns, as well as the need for efficiency, transparency, and innovation in financial products and services. This study aims to analyze international Islamic banking strategies when supporting economic progress including responding to fintech challenges and the advancing stages of digitalization. The research method used is descriptive qualitative using a literature study approach by examining scientific journals, several books, and a number of other references. The results of the analysis show that international Islamic banking can adjust through optimizing digital technology, strengthening business models to adjust some sharia values, and adding strategic partnerships. It is concluded that the success of international Islamic banking in experiencing the digital era is ensured by the ability to maintain a balance of technological innovation and sustainable implementation of sharia principles in its modern global financial system.